High-Intensity Intermittent Exercise and Autonomic Modulation: Effects of Different Volume Sessions - Castrillón, Carlos Iván Mesa [UNESP]; Miranda, Rodolfo Augusto Travagin [UNESP]; Cabral-Santos, Carolina [UNESP]; Vanzella, Lais Manata [UNESP]; Rodrigues, Bruno; Vanderlei, Luiz Carlos Marques [UNESP]; Lira, Fábio Santos [UNESP]; Campos, Eduardo Zapaterra (Thieme, 2017)
The aim of this study was to compare heart rate variability (HRV) recovery after 2 sessions of high-intensity intermittent exercise at different volumes (1.25 km [HIIE 1.25 ] and 2.5 km [HIIE 2.5 ]). 13 participants determined their maximal aerobic speed (MAS) and completed 2 HIIE (1:1 at 100% MAS) trials. The heart rate was recorded before and after each session. HRV indicators were calculated according to time (RMSSD and SDNN) and frequency (LF, HF and LF/HF ratio) domains. SDNN and RMSSD presented effect of test (F=20.97; p<0.01 and F=21.00; p<0.01, respectively) and moment (F=6.76; p<0.01 and F=12.30; p<0.01, respectively), without interaction. Even though we did not find an interaction effect for any HRV variables, the HIIE 2.5 presented a delay of only 5 min in HRV recovery, when compared to HIIE 1.25. However, the effects of the test (SDNN, RMSSD, LF-log, and HF-log) indicate higher autonomic stress during the entire recovery period. These findings may indicate that exercise volume interferes with HRV recovery. If so, physically active subjects may choose a lower volume exercise (i. e., HIIE 1.25) in order to promote similar physical fitness adaptations with lower loading on autonomic modulation.
Keywords: autonomic modulation; heart rate variability; High-intensity intermittent exercise; recovery